Entre el capitalismo dirigido y el Consenso de Washington. El Estado y las relaciones económicas de China con Brasil, Chile y México - León, José Luis (2012)
Economic relations between China and Latin America differ according to two subregions. Regarding Mexico and Central America there is a meaningful competition, while South America is benefiting from the high demand of commodities from China. While the relation has a lot to do with the market, the state also plays an important role. In China, resilient central planning and state intervention breeds significant effects on the relationship with Latin America. The Brazilian government has also sought to impinge upon the political and economic relations with China, while Mexico, more attached to laissez faire, has fewer will and instruments for this endeavor. Chile is an intermediate case in which the state still plays a promotional role through the ownership of mining companies and mechanisms of trade promotion.